Hardy Hibiscus for Florida Landscapes - Gary W. Knox; Rick Schoellhorn (EDIS)
Hardy hibiscus are an overlooked group of perennials with tremendous potential for the landscape. Hardy hibiscus are herbaceous perennial members of the genus, Hibiscus. They are large-flowered, fast-growing plants up to 15 feet tall and 4 to 8 feet wide. They are close relatives of the tropical hibiscus (Hibiscus rosa-sinensis) seen commonly in the landscapes of southern and central Florida. Unlike their tropical counterparts, however, hardy hibiscus are much more cold hardy, vigorous, and long lasting, and they have larger flowers. This document is ENH999, one of a series of the Environmental Horticulture Department, UF/IFAS Extension. Original publication date October 2005.